Caracterização da superfície e avaliação do desempenho mecânico e da translucidez de uma cerâmica de dissilicato de lítio avançada - Freitas, Júlia Saccol (2023)
This study was subdivided into Part I and Part II. For part I, discs (n = 15, 13.5 mm in diameter and 1.2 mm in thickness) were made from the following materials: 4Y-PSZ – zirconia stabilized with 4 mol% yttrium (IPS e.max ZirCAD A2); LD – lithium disilicate (IPS e.max CAD); ALD – advanced lithium disilicate (CEREC Tessera). The specimens were sintered/crystallized, analyzed by a rugosimeter (Mitutoyo SJ-410) and subjected to the biaxial flexural fatigue test using the step-test method (frequency 20 Hz; 10,000 cycles per step; initial stress 100 MPa; and step size of 25 MPa). Flexural fatigue strength (FFS) and number of cycles to failure (CFF) were recorded for statistical analysis. ALD had the lowest values for FFS, CFF (215 MPa and 11.908 cycles) and survival (p < 0.05). Regarding the Weibull module, ALD presented the lowest values (m = 6.63 for FFS; m = 1.27 for CFF). For surface roughness, ALD presented the lowest values of Ra (0.07 µm) and Rz (1. 05 µm) (p<0.05). Regarding hardness, LD and ALD have lower and similar values. Fractures originated in defects in the region observed at the tensile stress concentration. ALD has lower flexural fatigue strength, lower structural reliability and higher polishability. For study II, discs (n= 15, Ø= 10 mm and thickness 1.0 mm) of ALD (advanced lithium disilicate, CEREC Tessera, Dentsply Sirona), LD (Lithium Disilicate, IPS e.max CAD, Ivoclar), LSD (Lithium silicate-disilicate, Suprinity, Vita Zahnfabrik), 4Y-PSZ (Yttria-stabilized zirconia, IPS e.max ZirCAD MT, Ivoclar) were made from blocks/discs in color A2. The specimens were sintered/crystallized and subsequently analyzed by a rugosimeter (Mitutoyo SJ-410). The translucency analysis (TP00) was performed in a spectrophotometer (SP60, EX-Rite). The discs were cemented to epoxy resin disks with fiberglass, fatigue tested (Step-test), frequency of 20 Hz, initial cyclic load of 200 N for 5,000 cycles and load increments of 50 N every 10,000 cycles, up to disc failure. The load to fatigue failure (FFL) and CFF were recorded for statistical analysis. ALD showed lower survival (910 N and 147,000 cycles). Regarding the Weibull modulus, no differences were observed between the tested groups. ALD has translucency (TP00=28.14) similar to DL (28.27) and superior to LSD (25.51). Lithiumbased materials had greater translucency than 4Y-PSZ (TP00=8.62) (p < 0.05). For elemental composition, ALD appears to have a content similar to LD and LSD, for oxygen and silicon, and to LSD, for zirconium. The fractures originated on the cementation surface of the ceramic discs. ALD (Ra = 0.04 µm; Rz = 0.66 µm) showed the lowest surface roughness values (p < 0.05). ALD has a translucency and mechanical fatigue performance compatible with its indication for the fabrication of unitary anterior and posterior indirect restorations.